ANALISIS KUALITAS PELAYANAN KESEHATAN DI POLIKLINIK GIGI DAN MULUT UNIT PELAKSANA TEKNIS RUMAH SAKIT UMUM DAERAH UNDATA PROVINSI SULAWESI TENGAH - Abrianto Abrianto; Daswati Daswati; Nurhannis Nurhannis (CV. KAMPUS AKADEMIK PUBLISING, 2024)
In general, this research aims to analyze the quality of health services at the Dental and Oral Polyclinic, Technical Implementation Unit, Undata Regional General Hospital, Central Sulawesi Province. This type of research is qualitative research, namely research on data collected and expressed in the form of words and images, the words are arranged in sentences, for example sentences resulting from interviews between researchers and informants regarding a condition of the quality of health services at the Dental and Oral Polyclinic Unit. Technical Implementer of the Undata Regional General Hospital, Central Sulawesi Province. The basis of the research is qualitative to obtain more accurate data regarding phenomena regarding health services at the Dental and Oral Polyclinic. The theory used to determine service quality is the theory of Zeithaml, Parassuraman and Berry (Muninjaya, 2011) which includes five indicators, namely Tangible, Reliability, Responsiveness, Assurance, Empathy. The results of the research show that the quality of health services at the Dental and Oral Polyclinic of the Technical Implementation Unit of the Undata Regional General Hospital, Central Sulawesi Province is quite good, which can be seen from several interviews with 5 patients and 1 person in charge of the Polyclinic which has been run well. The indicators that have not been maximized are Tangibles, Reliability, and Assurance.